Prologue to the Symposium Obstetric Hemorrhages - Cabrera Ramos, Santiago (2020)
When obstetric emergencies are not treated adequately and in a timely manner, they represent the main cause of maternal morbidity and mortality in the world and, above all, in developing countries. It is important that every gynecologist is prepared to face potential hemorrhagic emergencies, establishing early warning systems, designing early responses and meetings of medical staff to identify the strengths and opportunities of the service provided.